Two new species of diminutive leaf-litter skinks (Squamata: Scincidae: Tytthoscincus) from Gunung Penrissen, Sarawak, Malaysia (northern Borneo) - Karin, Benjamin R.; Das, Indraneil; Bauer, Aaron M. (Zootaxa, 2016)
We describe two new species of skinks from Gunung Penrissen, Sarawak, Malaysia, in northern Borneo, Tytthoscincus batupanggah sp. nov. and T. leproauricularis sp. nov. Morphological and molecular analyses both corroborate the two new species as unique compared to all other Tytthoscincus and additional Sphenomorphus that are candidates for taxonomic placement in the genus Tytthoscincus. Despite their phenotypic similarity and sympatric distribution, a molecular analysis shows that the new species are not sister taxa and exhibit a deep genetic divergence between each of their respective sister taxa. We discuss how historical climatic and geographic processes may have led to the co-distribution of two relatively distantly related phenotypically similar species. In light of these discoveries, we also emphasize the importance of conserving primary montane tropical rainforest for maintaining species diversity.